Developing serverless applications : a practical introduction with Apache OpenWhisk - Camden, Raymond (O'Reilly Media, 2017)
Serverless computing has become a compelling option for many developers, evidenced by the many serverless platforms now available. Also known as Function as a Service, serverless computing lets developers deploy applications to the cloud without having to provision or manage a server--or pay for a server when it's not in use. You simply deploy the logic that comprises your application, while your cloud-based serverless provider handles everything else. With this practical report, author Raymond Camden shows you how to develop serverless code with Apache OpenWhisk, an open source serverless platform. You'll also get an introduction to OpenWhisk with Bluemix, a feature of IBM's cloud platform as a service suite. IBM, a major OpenWhisk supporter along with Adobe and Red Hat, provides an optional, easy-to-use way to deploy and host your OpenWhisk code. Get guidelines and rules for building and using actions, OpenWhisk's version of functions Use actions in production with OpenWhisk's Web Actions, the Bluemix API Management feature, or a REST API Combine actions into sequences, enabling several actions to work together in a single function Create, manage, and share packages for organizing your OpenWhisk actions.